Structural theory aspects of reflective practice in professional teaching activities (Pedagogical Horizons, 2024)
From a professional theory perspective, the teaching profession is constitutively linked to reflection in order to be able to meet the multitude of challenges. To achieve this, training requires the teaching of theoretical fundamentals and reflection techniques as well as suitable formats in which practical cases can be worked on reflexively under theoretical guidance. The aim of such a relationship between theory and practice is to promote the ability to work scientifically and to develop a research-oriented attitude. This article focuses on non-subject and topic-specific action problems that structure the pedagogical actions of teachers and can be processed casuistically. As a theoretical basis, the concept of profession is presented from the perspective of the structural theory approach, thereby justifying the need for the ability to reflect. Based on this, two aspects for professional reflective practice are generated, which can serve as foils for framing a reflection process by practitioners. On the one hand, these are the constitutive antinomies in teachers' actions and, on the other hand, the working alliances between teachers and learners, which are derived from a structural theory perspective. A proposed definition of professional reflection and the deconstructive reflection model are then presented. As a central element of professional qualification, theory-driven reflection should analyze practical school experiences using a structured reflection model with the aim of explicating viable alternative courses of action. In the final example of a practical school reflection, the case of a student is presented casuistically and the entanglements in antinomies and problematic working alliances inherent in the case are worked out from a structural theory perspective. Such a reflexive encounter of problematic teacher-student relationships is particularly suitable for the development of a pedagogical habitus.
Keywords: Structural theoretical professional approach; antinomies; working alliance; reflection concept; deconstructive casuistic